Inflammatory bowel disease induced by bimekizumab - Dominika Wietrzykowska-Grishanovich; Maciej Pleskacz; Radosław Kempiński (Gastroenterology Review)
Inflammatory bowel disease (IBD) is a chronic condition of the gastrointestinal tract, with a complex aetiopathogenesis in which genetic, immunological, and environmental factors are being discussed. The development of knowledge about molecular processes and the aetiology of diseases are made possible the implementation of modern therapies with biological drugs, which are a heterogeneous group of substances working by modulating the body’s immune response. Currently, biological medications are used in an increasing number of indications.